2016
DOI: 10.1017/s0963548315000383
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence in Preferential Attachment Networks

Abstract: We introduce a new model of competition on growing networks. This extends the preferential attachment model, with the key property that node choices evolve simultaneously with the network. When a new node joins the network, it chooses neighbours by preferential attachment, and selects its type based on the number of initial neighbours of each type. The model is analysed in detail, and in particular, we determine the possible proportions of the various types in the limit of large networks. An important qualitat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
133
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(136 citation statements)
references
References 33 publications
3
133
0
Order By: Relevance
“…However, Theorem 2.4 implies that the point of condensation also has positive probability of occurring at each of the endpoints 1 2 − s and 1 2 + s; since almost surely these values are not locations of any vertex, it follows that there is also a positive probability that there is no persistent hub. Figure 3 shows the results of two simulations for = −0.75 with different behavior: in the first simulation there is rapid convergence of Ψ n to a limit with condensation occurring via a persistent hub, whereas in the second Ψ n shows much slower convergence, apparently towards condensation at 1 2 + s. If ≤ − 7 8 , Theorem 2.3 implies that the location of the jump has full support on (0, 1).…”
Section: Middle Of Threementioning
confidence: 99%
See 3 more Smart Citations
“…However, Theorem 2.4 implies that the point of condensation also has positive probability of occurring at each of the endpoints 1 2 − s and 1 2 + s; since almost surely these values are not locations of any vertex, it follows that there is also a positive probability that there is no persistent hub. Figure 3 shows the results of two simulations for = −0.75 with different behavior: in the first simulation there is rapid convergence of Ψ n to a limit with condensation occurring via a persistent hub, whereas in the second Ψ n shows much slower convergence, apparently towards condensation at 1 2 + s. If ≤ − 7 8 , Theorem 2.3 implies that the location of the jump has full support on (0, 1).…”
Section: Middle Of Threementioning
confidence: 99%
“…for some > −1. Equation (1) gives the form of preferential attachment developed by Dorogovtsev, Mendes, and Samukhin in [7] as a generalization of the Barabási and Albert model found in [2], and we shall use this more general form. However, several of the papers referred to in this section, including [2], only consider the case = 0.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that in contrast to our results when starting from two vertices, a.s., all vertices but a finite number will be occupied by one of the two types. In a different follow up work, the authors of [2] introduced a model that coupled competition with the network growth and demonstrate that in this model often the two competitors will each occupy a linear fraction of the vertices even if one spreads faster than the other.…”
Section: Remarks and Follow Up Workmentioning
confidence: 99%